Modification of polyethersulfone ultrafiltration membrane using ultrasonic-assisted functionalized MoS2 for treatment of oil refinery wastewater - Arefi-Oskoui, Samira; Khataee, Alireza; Safarpour, Mahdie; Vatanpour, Vahid (Elsevier, 2020)
In this research, bulk MoS2 was exfoliated and functionalized using ultrasonic irradiation. The prepared nanolayered MoS2 was characterized using scanning electron microscopy (SEM), UV-Vis absorption, Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD) analyses. The nanolayered MoS2 was applied as a hydrophilic additive for modification of polyethersulfone (PES) ultrafiltration membrane. The MoS2/PES nanocomposite membranes with various contents of MoS2 were fabricated using non-solvent induced phase-inversion method. Finger-like morphology was observed for fabricated membranes in cross-section SEM images. According to the results of the atomic force microscopy (AFM) analysis, the optimum nanocomposite membrane represented highest average surface roughness and consequently highest efficient area for filtration compared with other nanocomposite membranes. The contact angle analysis confirmed hydrophilicity improvement of PES membrane by embedding nanolayered MoS2. The performance of the PES membrane was optimized in the presence of appropriate content of the hydrophilic nanolayered MoS2 (0.2 wt%). The pure water flux and flux recovery ratio of the 0.2 wt% MoS2/PES nanocomposite membrane were respectively 45% and 30% higher than that of the bare PES membrane. Finally, the optimized nanocomposite membrane was used for the treatment of oil refinery wastewater. The flux of the bare and optimum nanocomposite membrane was reached to 58% and 73% of their initial flux after 160 min of filtration. This confirmed better fouling resistance performance of optimum nanocomposite membrane compared with the bare one. The COD and the turbidity of the wastewater were decreased from 240 mg/L and 12.2 NTU to 40.8 mg/L and 2.1 NTU, respectively, after 160 min filtration by optimum nanocomposite membrane.
Keywords: Ultrafiltration; Sono-exfoliation; MoS2 nanosheets; Polyethersulfone; Nanocomposite